Independent Museums, Heritage, and the Shape of Museum Studies - Candlin, Fiona (Museum and Society, 2015)
Reflecting on the British heritage debates of the 1980s and 1990s, Robert Lumley asserted that they continue to influence Anglo-American definitions and perceptions of that subject. This article suggests that they had a correlative impact upon the parameters of museum studies. The museums founded during the 1980s were mainly small scale enterprises and they were devoted to many different topics, but commentators almost exclusively focused on the large independent organisations concerned with the recent industrial past. In doing so they associated the independent sector with ‘heritage’ rather than with established public museums. I maintain that this remains the case. Recent scholarship either considers independent museums in relation to the conceptual framework of the period or in terms of ‘community’, a discourse that is closely linked to recent developments in heritage studies. They are rarely, if ever, mentioned in analyses of architecture, professional practice, contemporary display or the role of museums. This omission effectively ascribes expertise and knowledge to public rather than independent institutions, maintains ingrained structures of social and cultural exclusion, and homogenises museum studies, limiting its concerns and scope.